Pengembangan E-Modul Laju Reaksi Berbasis Inkuiri Terbimbing Terintegrasi Virtual Laboratory Untuk SMA atau MA - Gusmadila Rahma Gevi; Andromeda Andromeda (Universitas Negeri Padang, 2019)
This study aimed to produce a reaction rate e-module based on guided inquiry integrated virtual laboratory and practical use in senior high school chemistry learning. The type of this research was Research and Development and the development model used was the 4-D model which consists of four stages: (1) define, (2) design, (3) development, (4) disseminate. This research was limited to the validity and practicality test. The validity test was carried out by 6 experts and limited trials to reveal the practicality done at SMAN 12 Padang. The research instrument used was in the form of a validity and practicality questionnaire which was analyzed using kappa moment (k) Data analysis showed that the average moment of kappa content validity was 0.89 with a very high validity category, while the average moment of kappa technical validity was 0.83 with a very high validity category. The average practical kappa moments from teachers and students were respectively 0.82 and 0.91 with a very high practicality category. These results were also supported by the analysis of students answers in answering critical questions, exercises, prelab questions, postlab questions, and worksheets in modules, with an average value of 82.63 percent. It can be concluded that the developed reaction rate e-module based on guided inquiry integrated with virtual laboratory is valid and practice to used on a learning process.